Critical review: assessing and seeking the intricacy or discrepancy of ulrich model transforming paradigm in organization human resource - Saleh, Nor Shela; Yaacob, Hashim Fauzy; Rosli, Mohd Shafie (MCSER Publishing, 2015)
"Human Resource (HR) transformation need to enlargement the influence in an organisation. Nonetheless, regard the admonition; change determinations that focus completely on improving human resource (HR) are bounce to fail. Dave Ulrich is the human resource founder and has qualified with evolving the human resource business mate, model and other dominant ideas in books including ""HR Champions"" and ""The HR Value Proposition"". Besides, Ulrich explains the six competencies HR be required to develop to accept the challenges of the worldwide economic crisis, globalisation, technological innovations and other change. His argument about Human resources rises to the people employed by an organization. Quantity the value of human resources verifies difficult due to lack of standard and traditional measures such as those related with permanent and liquid assets. For example, human resource cannot depreciate like physical resources, nor do they reflect the net value of an organization as financial resources accomplish. Human resources are just as important as physical and financial resources. Regrettably, organizational leaders and managers frequently overlook this actuality since human resources not used to reflect the organisation’s achievement."